Chemical and Sensory Profile of Grape Distillates Aged in Quercus alba Casks Previously Used for Sherry Wine or Brandy - Daniel Butrón-Benítez; Manuel J. Valcárcel-Muñoz; M. Valme García-Moreno; M. Carmen Rodríguez-Dodero; Dominico A. Guillén-Sánchez (Molecules)
This work investigates the influence of oak-cask ageing on the chemical composition and sensory profile of a variety of grape distillates. Wine spirit, wine distillate, neutral alcohol, and grape marc distillate were investigated. It is known that the characteristics of the ageing casks may have a considerable impact on the ageing process, so casks that had previously contained some type of sherry wine, sherry cask®, and casks that had previously contained brandy were studied. The results showed that ageing in either type of cask resulted in significant changes regarding volatile compound composition and a noticeable increase in phenolic and furfural compound content. Furthermore, sherry casks® contributed with sherry wine characteristic compounds that enriched the aromatic profile of the distillates, such as a greater increase in ethyl esters of organic acids. A less noticeable evolution was exhibited by the distillates with higher levels of congeners (wine spirit and grape marc distillate) when compared to wine distillate or neutral alcohol, where changes due to ageing were more evident. The sensory analysis confirmed that ageing significantly modified the organoleptic characteristics of all the distillates, with an increasing perception of certain notes such as oak, vanilla, spicy, and vinous when aged in sherry cask®.